Evaluation of micro leakage of two direct esthetic restorations with different preparation techniques - Eiman Abdullah Alharbi; Ahmed Mohamed Ahmed Elmarakby; Mukhlid Hameed Alshammari; Turki Saad Alharbi (Elsevier, 2019)
Objectives: In recent times, the term "minimal intervention dentistry" has coined to describe a new approach to the treatment of the disease of caries. This study was carried out to evaluate the marginal integrity of class V cavity in permanent posterior teeth prepared with different air abrasion parameters compared with classical rotary cavity preparation. Methods: A total number of 150 sound caries for free human posterior teeth were used in this study. Teeth were extracted for periodontal disease or orthodontic reasons and the average age of patients between 20 and 35 years. Teeth were divided according to the type of restoration into two main groups: Group I (n = 75) restored with low shrinkable posterior composite (P90) and Group II (n = 75) restored with Ketac nano ionomer (N100). Each main group was divided into five groups (n = 15), then each group was further subdivided into three subgroups (n = 5) according to the storage time (immediately, three months, and six months). All teeth would be tested at both occlusal and gingival margins of prepared class V cavity according to the method of cavity preparation. Results: A high significant difference was found in the mean ranks of micro-leakage at both occlusal enamel and gingival dentin walls among Groups 1-5 (p-value of <0.05). For main groups that restored with low shrinkable composite resin material (P90) and Ketac nano ionimer (N100), results revealed that scores of micro-leakage between (P90) or (N100) and both occlusal enamel or gingival dentin walls were significantly higher in group (AS1P1) than those in groups (B), (AS1P2), and (AS2P2) respectively. While no statistical significant difference was detected between groups (AS1P1) and (AS2P1). High scores of micro-leakage were detected at groups with six months, three months and immediately storage time respectively. Conclusion: Low shrinkable silorane based composite yielded better results of micro-leakage scores along the occlusal enamel and gingival dentin walls when the cavity of class V was prepared with air abrasion technique with large size alumina particles under high pressure at immediate storage time as compared with Ketac N100.